2003
DOI: 10.1002/qre.527
|View full text |Cite
|
Sign up to set email alerts
|

Accidents, often the result of an ‘uncontrolled business process’—a study in the (Dutch) chemical industry

Abstract: Often companies in the (petro-) chemical industry claim that all possible countermeasures against potential accidents have been taken and therefore accidents are unforeseeable. In this paper we question this statement by analysing the pre-warning signals (precursors) preceding a number of industrial accidents. 17 accidents that occurred in the (petro-) chemical industry have been investigated by exploring FACTS, an accident database containing information about industrial accidents worldwide. This paper will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…4.2.3 Double-loop learning. In addition to acknowledging discrepancies and contradictions in learning from incidents, some authors propose approaches aimed at bring about much desired but difficult to achieve double-loop learning (Sonnemans et al, 2003). Sonnemans for example examines root-cause analysis models as a form of double-loop process where existing, non-existing and inefficient norms are questioned (2008).…”
Section: What Kind Of Learning Process Is Adopted?mentioning
confidence: 99%
“…4.2.3 Double-loop learning. In addition to acknowledging discrepancies and contradictions in learning from incidents, some authors propose approaches aimed at bring about much desired but difficult to achieve double-loop learning (Sonnemans et al, 2003). Sonnemans for example examines root-cause analysis models as a form of double-loop process where existing, non-existing and inefficient norms are questioned (2008).…”
Section: What Kind Of Learning Process Is Adopted?mentioning
confidence: 99%
“…For example, Chung and Jefferson (1998) have developed an approach to integrate accident databases with computer tools used by chemical plant designers, operators, and maintenance engineers, permitting accident reports to be easily accessed and analyzed. In addition, Sonnemans, Korvers, Brombacher, van Beek, and Reinders (2003) have investigated 17 accidents that have occurred in the Netherlands petrochemical industries and have demonstrated qualitatively that had accident precursor information been recorded, with proper measures to control future occurrences, these accidents could have been foreseen and possibly prevented. Furthermore, Sonnemans and Korvers (2006) observed that even after recognizing accident precursors and disruptions, the operating systems inside companies often fail to prevent accidents.…”
Section: A Meel Et Al / Journal Of Loss Prevention In the Process Imentioning
confidence: 99%
“…Researchers have successfully integrated human factors components in accident investigation tools [1] or have developed an elaborate model in which organisational and technical elements are coupled together [2,3]. These approaches are useful for either the organisation that wishes to learn more from accidents or for researchers who are studying connections between two separate worlds of scientific subjects.…”
mentioning
confidence: 99%